Membangun Jiwa Kepemimpinan di Era Digital: Kegiatan Sosialisasi di MAS Kepala Hilalang - Nurdiani, Silvana; Fajrina, Rahma Melisha; Darmansyah, Darmansyah; Suryanti, Suryanti; Ramadani, Helsi Zulfan (Pakis Journal Institute, 2025)
The rapid development of digital technology demands that young generations possess adaptive, visionary leadership skills and the ability to utilize digital advancements wisely. This community service activity aimed to foster and strengthen leadership attitudes among students at MAS Kepala Hilalang through interactive and practical socialization activities. The implementation methods included preliminary observation, material delivery through lectures and discussions, as well as role-playing simulations to train digital leadership. The results of the activity showed an increase in students' understanding of leadership concepts in the digital era, including the importance of digital literacy, online communication skills, and data-driven decision-making. Moreover, students demonstrated high enthusiasm in participating in leadership simulations and group discussions. This activity proves that participatory and contextual socialization programs can positively impact students’ character formation, particularly in developing leadership skills relevant to the digital transformation era. It is expected that this initiative can be sustained and adopted by other educational institutions as part of technology-based character education efforts.